Correlation of symptomatic enterovirus infection and later risk of allergic diseases via a population-based cohort study. Issue 4 (January 2017) - Lee, Zon-Min; Huang, Ying-Hsien; Ho, Shu-Chen; Kuo, Ho-Chang
Abstract : Abstract: Infants who are exposed to the rhinovirus or respiratory syncytial virus are at a higher risk of subsequently developing wheezing or asthma. This study aims to determine whether preschoolers with a history of symptomatic enterovirus infection are at an increased risk of developing allergic diseases or not. We used data from the Taiwan National Health Insurance Research Database from 1999 to 2006 for this nationwide population-based cohort study. The subsequent risks for allergic diseases, which included asthma (International Classification of Diseases [ICD]-9: 493.X), allergic rhinitis (AR; ICD-9 CM code 477.X), and atopic dermatitis (AD; ICD-9-CM code 691.X), were compared between herpangina (ICD-9: 074.0) and hand, foot, and mouth disease (HFMD; ICD-9: 074.3) throughout the follow-up period using the Cox proportional hazards model. In this database, 12, 016 neonates were born between January 1999 and December 1999. Among them, we further evaluated 8337 subjects; 3267 children infected with either herpangina or HFMD served as the study cohort, and the other 5070 children made up the comparison cohort. Children in the herpangina group had a higher risk of developing AR and AD, with adjusted hazard ratios of 1.15 (1.02–1.30, 95% CI) and 1.38 (1.17–1.63. 95% CI), respectively, while children suffered from HFMD had decreased risks of asthma, with an adjusted hazard ratio of 0.76 (0.63–0.93, 95% CI). Children who previously suffered from herpangina experienced an increased risk of subsequently developing AD and AR. Meanwhile, children who had suffered from HFMD experienced a decrease in the subsequent occurrence of asthma compared to the general population.